Copper Deficiency: An Overlooked Cause of Anemia and Leucopenia (Global Journal of Medical Research, 2020)
Introduction-Copper deficiency (hypocupremia) is an acknowledged but often overlooked cause of anemia and leukopenia (1-4). It is recognized as a frequent cause of hypochromic microcytic anemia, leukopenia, and neuropathy. Copper deficiency anemia has been reported after gastric resection (e.g., Roux-en-Y) (1, 5, 6), excessive zinc consumption (1, 6-9), and in patients with short bowel syndrome receiving total parenteral or enteral nutrition lacking adequate copper supplementation (1, 2). We report a case of vitamin B12, and iron refractory severe anemia and leucopenia with history of Roux-en-Y surgery. Myelodysplastic syndrome was suspected. Bone marrow biopsy was consistent with copper deficiency and serum copper levels were undetectable. The patient experienced complete hematological recovery after copper replacement therapy.